Southern Politics in the 1990s - Lamis, Alexander P. (Book collections on Project MUSE., 1999)
"During the 1990s, the Republican party surged to majority status in the South after two decades of struggling unevenly to become established in the formerly one-party Democratic section of the country. In this comprehensive, up-to-date study, seasoned observers tell the story of the GOP's remarkable advance at the regional level and in each of the eleven states of the former Confederacy, effectively capturing the current partisan dynamics at work throughout Dixie."--Jacket.